Increased frequency of FBN1 frameshift and nonsense mutations in Marfan syndrome patients with aortic dissection. Issue 1 (12th December 2019) - Xu, Shijun; Li, Lei; Fu, Yuwei; Wang, Xin; Sun, Hairui; Wang, Jianbin; Han, Lu; Wu, Zining; Liu, Yongmin; Zhu, Junming; Sun, Lizhong; Lan, Feng; et al.
Abstract: Background: Marfan syndrome (MFS) is an inherited connective tissue disease that mainly involves Fibrillin‐1 (FBN1) mutations and aortic manifestations. In this study, we investigated the correlations between the FBN1 genotype–phenotype and aortic events (aortic dissection and aortic aneurysm) in patients with Marfan syndrome. Methods: Genotype and phenotype information was evaluated in 180 patients with MFS. DNA sequencing was performed on each patient. According to the clinical manifestation, these patients were split into two groups: the aortic dissection group and the aortic aneurysm group. Aortic wall tissue was obtained from Marfan patients who underwent surgery and was used for staining. Results: A total of 180 patients with FBN1 mutations were grouped into four categories: 90 with missense mutations, 32 with splicing mutations, 29 with frameshift mutations, and 29 with nonsense mutations. There was a significantly higher frequency of frameshift and nonsense mutations observed in aortic dissection than in aortic aneurysm (25.58% vs. 4.35%, p = .005; 25.58% vs. 8.70%, p = .033, respectively;), while missense mutations showed a higher frequency in aortic aneurysm than in aortic dissection (69.57% vs. 32.56%, respectively; p < .001) and a higher rate of lens dislocation (34.78% vs. 13.95%, respectively; p = .008). Pathological staining showed that elastic fibers were sparser in patients with a frameshift and nonsense mutations, and the smooth muscle cells were sparser and more disorganized than those observed in patients with missense mutations. Conclusion: This study showed that FBN1 gene frameshift and nonsense mutations are more common in patients with aortic dissection and may have meaningful guidance for the treatment of Marfan syndrome patients. Abstract : This study increase our understanding of the FBN1 gene mutation spectrum in Chinese patients with MFS. We found that frameshift mutations were more common in patients with aortic dissection and that the aortic wall structure contained fewer elastic fibers and fewer and more disordered smooth muscle cells.